A study on the development of red dragon fruit (Hylocereus polyrhizus) jam and marmalade - Rizardo, Jenny Vi Ynion (2013.)
Red dragon fruit (Hylocereus polyrhizus) (RDF) was characterized and utilized in jam and marmalade making.
Sotech thesis.
Keywords: Red dragon fruit